Collage of cases and brief review of the laboratory diagnosis and molecular testing in autoimmune haemolytic anaemia - Harkiran Arora; Shalini Trivedi; Pooja Jain; Udita Singhal; Arunpreet Kaur; Aditi Raina (Journal of Family Medicine and Primary Care, 2024)
Autoimmune haemolytic anaemia (AIHA) is an acquired heterogenous clinical entity with variable presentations like acute haemolysis or mild, chronic haemolysis compounded with acute exacerbation in winters or fatal uncompensated haemolysis. A step-wise approach to the diagnosis and characterisation of AIHA should be undertaken, firstly the diagnosis of haemolysis followed by the establishment of immune nature with the aid of direct agglutination tests (DAT). Simultaneously the other causes of immune haemolysis need to be excluded too. In light of advancements in diagnostics, a wide array of investigations can be used like absolute reticulocyte count, bone marrow responsiveness index to establish the evidence of haemolysis, sensitive gel technology, enhanced DAT assays, e.g., modified DAT with low ionic strength saline solution (LISS) at 4°C, DAT assays utilizing reagents such as anti-IgA and anti-IgM and DAT by flowcytometry, to detect RBC bound autoantibodies (Abs) and monospecific DAT to establish immune causes of haemolysis and characterisation of the autoantibodies. The compensatory role of bone marrow and synchronous pathologies like clonal lymphoproliferation, dyserythropoiesis, fibrosis are important factors in the evolution of the disease and aid in the customisation of treatment modalities. The laboratory work up should aim to diagnose underlying diseases like chronic lymphoproliferative disorders, autoimmune disorders and infectious diseases. Also, tests like autoimmune lymphoproliferative syndromes (ALPS) screening panel and Next-generation sequencing (NGS) panel for RBC membrane disorders, RBC enzymopathies, and congenital dyserythropoietic aneamia have found their place. It is incumbent upon the clinicians to use the all-available diagnostic modalities for the accurate diagnosis, prognostication and customisation of the therapy.